An investigation of the friction and wear behavior of soybean biodiesel. (March 2019) - Xiao, Huaping; Zou, Huiyu; Liu, Shuhai; Li, Chengming
Abstract: Biodiesel has attracted more and more attention worldwide due to increasing environmental concerns. In this study, the tribological performance of soybean biodiesel was evaluated through HFRR. Besides steel-steel contact, steel-ceramic and steel-diamond contacts were also investigated since coating with ceramic and diamond materials is popular to improve tribological performance in diesel engine. Results reveal that in contrast to steel and ZrO2, diamond coating is effective in friction and wear reduction. Wear scar sizes of steel balls for steel-steel contract decrease with increasing concentration of biodiesel. However, higher concentration of biodiesel produces larger wear scar when steel balls were mated with ZrO2 . Results indicate that diamond coating is effective to improve tribological performance while ZrO2 is not applicable in biodiesel environment. Highlights: The tribological performance of soybean biodiesel was evaluated for steel-steel, steel-ceramic, and steel-diamond contacts. Wear scar sizes of steel balls for steel-steel contract decrease with increasing concentration of biodiesel. Higher concentration of biodiesel produces larger wear scar when steel balls were mated with ZrO2 . Diamond coating is effective to improve tribological performance while ZrO2 is not applicable in biodiesel environment.